2021
DOI: 10.1111/jam.14986
|View full text |Cite
|
Sign up to set email alerts
|

Fish infections associated with the genus Aeromonas : a review of the effects on oxidative status

Abstract: The aim of this review was to summarize the current knowledge regarding the effects of aeromonosis on fish oxidative status. The bibliographic survey was carried out on the research platforms: Scopus and Science Direct. The keywords 'Aeromonas', 'fish' and 'oxidative status' (or 'oxidative stress', 'oxidative damage' and similar terms) were used. Scientific papers and short communications were considered. Studies involving fish aeromonosis and enzymatic or non-enzymatic markers of oxidative status were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…(2018) found that reactive oxygen species have increased in silver catfish Rhamdia quelen exposed to A. caviae infection; they also reported increased activity of antioxidant enzymes than in non‐infected fish. Also, Bandeira Junior and Baldisserotto (2020) mentioned that reactive oxygen species are considered good indicators for oxidative stress during Aeromonas infection in fish; fish fight bacterial infection by releasing reactive oxygen. They reported that Aeromonas infection induced the activity of the antioxidant enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) found that reactive oxygen species have increased in silver catfish Rhamdia quelen exposed to A. caviae infection; they also reported increased activity of antioxidant enzymes than in non‐infected fish. Also, Bandeira Junior and Baldisserotto (2020) mentioned that reactive oxygen species are considered good indicators for oxidative stress during Aeromonas infection in fish; fish fight bacterial infection by releasing reactive oxygen. They reported that Aeromonas infection induced the activity of the antioxidant enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…In the genera of freshwater and brackish water fish, Infectious Hematopoietic Necrosis Virus ( IHNV ), Lymphocystis Disease Virus ( LCDV ), Pseudomonas, Citrobacter , Proteus, Streptococcus, Edwardsiella, Staphylococcus, and different species of Vibrio , are considered as the most life-threatening infections. One of the major diseases in the fish is caused by Aeromonas hydrophila , which is colonized in the GI tracts of the fish, leading to severe hemorrhagic septicemia and enteritis [ 10 ]. Current therapeutic strategies for the fish mainly include the usage of chemotherapeutic drugs like antibiotics and vaccination [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the variations of bacterial communities in healthy fish ( de Bruijn et al., 2018 ), the effect of environmental factors on intestinal bacteria ( Wang et al., 2018 ) and interactions between intestinal bacteria and immune response ( Gómez and Balcázar, 2008 ; Nie et al., 2017 ) were also drew much interest recently. The immune system impacts the ecology of commensal bacterial communities, and the bacteria were also found to be able to elicit a mild inflammatory reaction and activate the innate immune response after they were colonized in zebrafish larvae ( Montalban-Arques et al., 2015 ), and induce oxidative stress ( Yin et al., 2015 ; Bandeira Junior and Baldisserotto, 2021 ). Some intestinal bacterial taxa were also reported as health indicators in marine invertebrate species ( Xiong et al., 2015 ; Huang et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%